Health effects of attending a public swimming pool: follow up of a cohort of pupils in Paris. Issue 6 (December 1993) - Momas, I; Brette, F; Spinasse, A; Squinazi, F; Dab, W; Festy, B
Abstract : OBJECTIVES--This study aimed to determine the health effects of attending a well-kept school swimming pool maintained according to French public health regulations. METHODS--This prospective month long study was carried out on a randomised sample of pupils aged 5 to 18 years who attended a private French school with two swimming pools. The children surveyed, helped by their parents, had to fill in questionnaires about their bathing habits and symptoms during the survey period. Inspections of the pool complex were made and these included physicochemical and bacteriological analyses of the pools' water. PARTICIPATION--The response rates achieved were 70% at primary and middle school levels but only 25% in the high school pupils. Because of this older teenagers were excluded from the final analysis (of 246 children). RESULTS--Compared with non-bathers, bathers experienced fatigue and eye irritation significantly more often (p < 0.001). The eyes were red (38% of bathers) and/or watery (16%) after swimming but this resolved spontaneously within 24 hours. Bathing behaviour (bath duration, head immersion, wearing swimming goggles) did not affect these incidence rates noticeably. There were no differences between bathers and non-bathers with regard to other symptoms, especially otolaryngological ones. This survey does not allow definite conclusions to be made about verrucas because 22% of non-bathers were exempted from swimming because of verrucas that they might have caught previously in a pool. CONCLUSIONS--Except for verrucas, the methodology was adequate and daily self reporting of symptoms was feasible. This college largely recruits pupils from higher social classes and is not therefore representative of schools in Paris.